Development of IoT portable device for saline water monitoring in Bang Kachao Area of Thailand - Thanavit Anuwongpinit; Sakditat Sutthinoon; Pinit Tanachaichoksirikun; Boonchana Purahong (My University, 2023)
Abstract This research developed a portable water salinity measurement device using internet of things technology to support farmers in Bang Kachao area in Samut Prakan province, Thailand, to select quality water for cultivation and consumption. The system hardware consists of a microcontroller ESP32 with a GPS module and an electrical conductivity sensor with an analog-to-digital conversion module for saline water measurement. This device can connect to an internet system via a Wi-Fi network and MQTT protocol to transmit the data of saline water value and measuring location to the cloud system. In the cloud system, the node-red system software is installed as a data gateway for device interfacing. In addition, a node-red dashboard is used to collect data from a portable device and previously installed water quality monitoring station for visualizing a portable device location and saline water data. This dashboard is a web page that allows people to monitor the water situation in the area that is suitable to use.
Keywords: Interfacing; Dashboard; Saline water; MQTT; Water Quality Monitoring Technologies